ZAKAT DAN TUJUAN PEMBANGUNAN BERKELANJUTAN DI KALIMANTAN TIMUR - Yanti, Dharma; Sanjaya, Lilik Intan; Wardah, Wardah (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study looks at how zakat helps East Kalimantan Province achieve the Sustainable Development Goals (SDGs). The SDGs are a global framework that covers a number of topics, such as social welfare, economics, health, and environmental sustainability. with a primary goal of reducing poverty to zero by 2030. In Indonesia, zakat has significant potential as an Islamic economic instrument to support SDG targets, especially in poverty alleviation and reducing social inequality. However, zakat's implementation in national poverty reduction policies has not been fully integrated into the country's development system. The significance of zakat as a formal instrument for attempts to reduce poverty is the foundation of this study. Through a variety of community empowerment programs, philanthropic zakat groups in East Kalimantan, including as BAZNAS, LAZ DPU, and Rumah Zakat, have actively assisted the government in achieving Sustainable Development Goal (SDG) indicators. Examining how zakat can support the achievement of the SDGs is the aim of this research. particularly in regional contexts, and how zakat institutions integrate their programs with SDG goals. This study does qualitative research using a case study methodology. Interviews, observations, and documentation from zakat charity groups were used to collect data in East Kalimantan. The research findings show that zakat programs managed by these institutions significantly overlap with several SDG indicators, such as poverty reduction, improving access to education, and public health. However, the level of integration by each institution varies; some have systematic and comprehensive mechanisms, while others are still in the development phase. In order to accelerate the achievement of the Sustainable Development Goals (SDGs), this study improves understanding of the strategic significance of zakat in fostering sustainable development in East Kalimantan and provides recommendations for strengthening cooperation between zakat institutions and governmental entities